Exploring Emoji-Mediated Communication to Enhance Emotional Expression, Engagement, and Digital Literacy in Online Language Learning - Aditya Wicaksono; Raveenthiran Vivekanantharasa (International Forum of Researchers and Lecturers, 2024)
The rapid development of digital technology has reshaped communication practices in online learning, particularly in language education. Emojis, as a visual symbol widely used in digital interactions, have the potential to enrich emotional expression and participation, but their role in educational contexts remains insufficiently explored. This study aims to investigate how emojis influence students’ emotional expression, engagement, and digital literacy in online language classrooms. To achieve this, a qualitative observational design was employed, focusing on university students participating in online language courses. Data were collected from authentic digital interactions, including chat messages, discussion forums, and collaborative platforms, and were analyzed through content analysis to identify the communicative and pedagogical functions of emojis. The findings indicate that emojis help clarify emotional expression, support comprehension of messages, and encourage active student participation in online discussions. These results demonstrate that emojis not only serve as supplementary tools for digital communication but also contribute to creating a more engaging and supportive learning environment. Synthesizing the main ideas, this study extends the understanding of digital communication theory by highlighting the pedagogical value of emojis beyond their informal use on social media. In conclusion, emojis play a crucial role in strengthening interaction, fostering emotional presence, and enhancing learning outcomes in online language education. The study recommends integrating emojis into digital teaching practices while encouraging further research on cultural variation, learner levels, and diverse digital platforms to maximize their educational potential.